Size distribution, characteristics and sources of heavy metals in haze episod in Beijing - Duan, Jingchun; Tan, Jihua; Hao, Jiming; Chai, Fahe (Journal of environmental sciences (China), 2014)
Size segragated samples were collected during high polluted winter haze days in 2006 in Beijing, China. Twenty nine elements and 9 water soluble ions were determined. Heavy metals of Zn, Pb, Mn, Cu, As, Cr, Ni, V and Cd were deeply studied considering their toxic effect on human being. Among these heavy metals, the levels of Mn, As and Cd exceeded the reference values of National Ambient Air Quality Standard （GB3095-2012） and guidelines of World Health Organization. By estimation, high percentage of atmospheric heavy metals in PM2.5 indicates it is an effective way to control atmospheric heavy metals by PM2.5 controlling. Pb, Cd, and Zn show mostly in accumulation mode, V, Mn and Cu exist mostly in both coarse and accumulation modes, and Ni and Cr exist in all of the three modes. Considering the health effect, the breakthrough rates of atmospheric heavy metals into pulmonary alveoli are： Pb （62.1%） 〉 As （58.1%） 〉 Cd （57.9%） 〉 Zn （57.7%） 〉 Cu （55.8%） 〉 Ni （53.5%） 〉 Cr （52.2%） 〉 Mn （49.2%） 〉 V （43.5%）. Positive matrix factorization method was applied for source apportionment of studied heavy metals combined with some marker elements and ions such as K, As, SO42- etc., and four factors （dust, vehicle, aged and transportation, unknown） are identified and the size distribution contribution of them to atmospheric heavy metals are discussed.